Tracking the development of lean and fat areas of the arm from childhood to adulthood in a cohort of the Ellisras longitudinal study - Mabogoana, Mankopodi Mahlako Khomotso (My University, 2024)
Undernutrition is a major public health problem in Africa. The risk of underweight is associated with a negative impact on children’s health, growth and development in later life. Upper arm composition is used to determine the prevalence of undernutrition. The use of upper arm composition reflects body protein and calorie reserves. However, there is a paucity of data on the upper arm composition of children from African countries. This study aimed to investigate the development of fat and lean areas of the arms and seasonal variation of upper arm fat and lean areas from childhood into young adulthood. Mid-upper arm circumference (MUAC), triceps and biceps skinfold measurements were measured according to the recommended anthropometric standard procedures. The measurements were collected during the autumn (April – May) and spring (October – November) seasons from 1997 to 2003. The total upper-arm area (TUA), arm fat area (AFA) and arm muscle area (AMA) were calculated. A total of 911 boys and 852 girls, aged 4 to 17 years participated in the survey in 1997 were included in this study. This was a retrospective data analysis study. Data was analysed using the Mann-Whitney U test to examine sex and age differences in anthropometric characteristics in autumn and spring. Ellisras boys and girls had a low mean value in AMA development when compared with the NHANES (National Health and Nutrition Examination Survey III) reference population. Moreover, the Ellisras girls had higher AMA when compared to boys of the same age. Furthermore, there was no clear pattern in the development of MUAC among Ellisras children when compared to the reference population. Contrary to other findings Ellisras children had a higher AFA when compared to the NHANES III reference population. The generalised estimate equation (GEE) was used to test the relationship between autumn and spring according to AFA, AMA and MUAC. The prevalence of undernutrition was low by AFA at 3.9% in boys when compared to girls at 13.2%, high when using AMA at 95.1% and 82.1% in boys and girls respectively. In addition, the prevalence of undernutrition by MUAC was 58.0% and 49.5% for boys and girls respectively. Boys aged between 8 – 11 years had a significant (p-value = 0.020) positive association in AFA with β = 0.47, (95% CL: 0.07; 0.82) and girls of the same age also had a positive significant association (p-value = 0.001), in AFA with β = 1.30, (95% CL: 0.58; 2.03) in spring as compared to autumn. Furthermore, there was a significant median difference between arm fat area (AFA) and arm muscle area (AMA), in autumn and spring. There was seasonal variation observed between the seasons over time, from mid-childhood to the adolescent stage. There was a positive significant (p < 0.001) association between the first AFA, AMA and MUAC and the subsequent measurements for both boys and girls, throughout the period. AFA of β = 0.01, (95% CL: 0.00; 0.01) and β = 0.03, (95% CL: 0.03; 0.04) for boys and girls respectively. Moreover, girls had an elevated beta range when compared to boys. A similar trend was observed with AMA β = -0.01, (95% CL: -0.01; 0.01) and β = 0.04, (95% CL: 0.03; 0.04) for boys and girls respectively. However, MUAC for boys was elevated β = 0.03, (95% CL: 0.02; 0.04) when compared to girls β = 0.01, (95% CL: 0.00; 0.01). The tracking coefficient between the initial measurements and the subsequent measurements was higher for AMA and AFA when compared to MUAC. This could be supported by slightly higher tracking coefficients in Ellisras girls compared to boys over time. The six-year duration of the study with measurements carried out twice yearly not only provides accurate tracking measurements of the arm anthropometry. In conclusion, the findings of this study suggest that there high prevalence of undernutrition found in this study. Furthermore, there was a substantial seasonal variation in the growth and development of fat and lean arm areas among the Ellisras children. Arm anthropometry may be a valuable way to evaluate the nutritional status of children. On the other hand, there are a limited number of studies available, and there are limited longitudinal studies that have investigated the development of MUAC, arm muscle and fat area over more or less the same length where the current study was carried out.
Thesis (M.Sc.(Physiology)) -- University of Limpopo, 2024
Keywords: Lean mass; Fat mass; Mid upper arm circumference; Arm anthropometry; Undernutrition; Rural South African children; Seasonal variation; Arm fat area; Arm muscle area; Leanness; Rural children --South Africa; Anthropometry; Children -- Growth